ANALISIS KEKUATAN PEGAS DAUN KIJANG SERI 5k SEBELUM DAN SESUDAH MODIFIKASI PENEKANAN - Margono Sugeng; Rizki Adi Kurniawan (Bina Teknika, 2018)
Leaf spring is one of the components contained in the rear suspension system and made from high carbon carbon steel. Nowadays, many people do leaf spring modifications, one of them is by the pressing process, but many of the vehicle owners modify it excessively and finally leaf springs broken. Therefore to know how the strength of leaf springs is done by testing the chemical composition test, metallographic test, hardness test and tensile test, the test is done in PT.IWWI located in tangerang area. The sample used to perform the test consisted of 4 samples, namely sample A, sample B, sample C and sample D, taken from each spring number 3 which has been modified as much as 2 cm and that has not been modified. From the four tests obtained results from testing the chemical composition of carbon content contained in sample C is highest with the value of carbon content contained 0.7719. From the hardness testing of sample which has the highest hardness value is sample C with hardness value 111.06 [kgf]. and from the sample tensile strength test which has the highest tensile strength value is sample B with a tensile strength value of 1408.75 [N / mm2].